2022
DOI: 10.1021/acs.jmedchem.2c01319
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of 5-Formyl-pyrrolo[3,2-b]pyridine-3-carboxamides as New Selective, Potent, and Reversible-Covalent FGFR4 Inhibitors

Abstract: The FGF19-FGFR4 signaling pathway has been extensively studied as a promising target for the treatment of hepatocellular carcinoma (HCC). Several FGFR4-selective inhibitors have been developed, but none of them receives approval. Additionally, acquired resistance caused by FGFR4 gatekeeper mutations is emerging as a serious limitation for these targeted therapies. Herein, we report a novel series of 5-formyl-pyrrolo[3,2-b]pyridine derivatives as new reversible-covalent inhibitors targeting wild-type and gateke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
(115 reference statements)
0
14
0
Order By: Relevance
“…Additionally, our previous studies had demonstrated that an (R)-3,5-dichloropyridine-4-yl ethoxy group favorably increased cellular activity by introducing additional interactions with FGFR4 based on a pan-FGFR inhibitor, LY2874455. 27 Thus, replacement of the methoxyethylamino group of 8l with an (R)-3,5-dichloropyridine-4-yl ethoxy group led to compound 8m. While compound 8m showed a 2-fold decrease in FGFR4 biochemical inhibitory 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, our previous studies had demonstrated that an (R)-3,5-dichloropyridine-4-yl ethoxy group favorably increased cellular activity by introducing additional interactions with FGFR4 based on a pan-FGFR inhibitor, LY2874455. 27 Thus, replacement of the methoxyethylamino group of 8l with an (R)-3,5-dichloropyridine-4-yl ethoxy group led to compound 8m. While compound 8m showed a 2-fold decrease in FGFR4 biochemical inhibitory 2).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our effort to discover novel reversible-covalent FGFR4 inhibitors, we identified the 5-formyl-pyrrolo [3,2-b]pyridine-3carboxamide (5-PPC, 8a) as a selective FGFR4 inhibitor starting point for a scaffold-hopping strategy. 27 Compound 8a possesses a pyrrolo [3,2-b]pyridine core instead of the original tetrahydronaphthyridine core. We found that compound 8a displayed nanomolar activity against FGFR4 in a biochemical assay (IC 50 = 10.0 nM) and suppressed the growth of engineered Ba/F3 cells harboring FGFR4 (Ba/F3-FGFR4) with an IC 50 value of 11.8 nM, while sparing FGFR1/2/3 (IC 50 > 10 μM).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations